The influence of digital leadership competencies on employee innovative work behavior in an electrical and electronic manufacturing company - Tan, Tsze Wen (2021)
In recent years, Malaysia has undergone rapid changes due to Industry Revolution 4.0. Therefore, innovation is highly required in many industries, specifically Electrical and Electronics (E&E) manufacturing companies. This study aims to investigate the impact of digital leadership competencies on employees’ innovative work behavior in Penang E&E manufacturing company. This research uses a quantitative approach to study the relationship between variables, and the unit of analysis is middle-level employees in an E&E manufacturing company. The sample is selected through the purposive sampling technique. Besides that, the link to the online questionnaire, “Google Form”, is then shared with the assigned HR representative through electronic mail. The data were collected from 112 middle-levels employees of E&E manufacturing company in Penang in a cross-sectional survey and were analysed using the statistical package for the social sciences technique (SPSS). The result of hypotheses testing confirmed that E-Communication competency has a significant positive influence on employee innovative work behavior. The study explained 45 per cent of the variance in innovative work behavior. The research findings suggested the importance of E-Communication competency in nurturing innovative work behavior among employees in that company. This study focuses on an E&E manufacturing company in Penang due to resource limitations; thus, the survey was using crosssectional. Therefore, further studies may include longitudinal studies. Hence, theoretical and practical implications, limitations and suggestions for future research are discussed and highlighted in this study.